SISTEM INFORMASI MANAJEMEN DI SUB BAGIAN HUBUNGAN MASYARAKAT DAN INFORMASI UNIVERSITAS ISLAM NEGERI SULTHAN THAHA SAIFUDDIN JAMBI - Rizkika Rizkika; Siti Raudhatul Jannah; Aris Dwi Nugroho (JMiE (Journal of Management in Education), 2020)
This thesis discusses Management Information Systems in the Public Relations and Information Sub Division of the Sulthan Thaha Saifuddin Jambi State Islamic University. This research is a qualitative study, while data collection is done by interviewing, documenting, and observing, analyzing through data reduction, data presentation, and drawing conclusions. This research was conducted at Sulthan Thaha Saifuddin Jambi State Islamic University with the subject of the research being the Head of Sub Division of Public Relations and Information, while additional information was determined by the Staff of Public Relations and Information. The study found a Management Information System in the Public Relations and Information Sub Division of the Sulthan Thaha Saifuddin Jambi State Islamic University, namely the application of a management information system in the public relations and information sub-section, which was carried out by means of an offline system and the second via online. Supporting factors for the implementation of management information systems in the public relations and information sub-sections namely having their own website and the inhibiting factors that occur when inputting news are network dependency, other obstacles such as in the individual staff section because each staff has different majors backgrounds, lack of coordination between organizers and public relations and lack of cameras to cover events. Efforts are made to provide 1 camera for 1 staff so that when there are activities staff have their own cameras, attempt to add public relations staff, then public relations establish communication links between public relations with the faculty and the University through a letter that is making a letter to the faculty and university.